Decision-making and power in the British Conservative Party a study of the Indian problem 1929-1934 - Ghosh, S.C. (Suresh Chandra) (Oceania Publishing House, 1972)
The book makes an original theoretic contribution to the study of the decision-making and power in a large political party. With a focus on decision-making, with a detailed study of the Conservatives' dissensions on the Indian problem since 1917, the author shows that the distribution of power in the British Conservative Party is diffused and tends to be specific to issues, and that the power-situation is made complex and obscure by the active participation of people and interests other than the formal followers in a given decision-making process.